1976
DOI: 10.1016/s0022-5347(17)58919-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Urethral Syndrome with Triamcinolone Acetonide

Abstract: A new method for the treatment of the urethral syndrome is presented. Therapy involves the submucosal injection of triamcinolone acetonide around Skene's glands to decrease inflammation and scarring. It is a simple office procedure, while all other therapeutic modalities are surgical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In a Swedish randomized study from 1972, urethral dilatation combined with instillation of chloromycetin-hydrocortisone (very low potency corticosteroid US class VII, Europe class I) was shown to relieve or remove symptoms in 44 % of women with symptoms of cysto-urethritis without concurrent findings of urinary tract infection [28]. In 1976 an American study presented a very good response in 54 women treated with sub-mucosal injections of the corticosteroid triamcinolone acetonide (moderate potency corticosteroid US class III, Europe class II) around the paraurethral glands [29]. In these studies no side effects were observed or mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…In a Swedish randomized study from 1972, urethral dilatation combined with instillation of chloromycetin-hydrocortisone (very low potency corticosteroid US class VII, Europe class I) was shown to relieve or remove symptoms in 44 % of women with symptoms of cysto-urethritis without concurrent findings of urinary tract infection [28]. In 1976 an American study presented a very good response in 54 women treated with sub-mucosal injections of the corticosteroid triamcinolone acetonide (moderate potency corticosteroid US class III, Europe class II) around the paraurethral glands [29]. In these studies no side effects were observed or mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…However, lower urinary tract symptoms are also common in females [1,2,6,15,19]. The idea that outlet obstruction in women may cause frequency and urgency has long been accepted.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, pollakisuria, urgent straining and dysuria with the lack of objective urological findings, is known as urethral syndrome [1,4,6,8,15]. This myriad of symptoms may also be coined urgency/frequency syndrome, psychosomatic cystitis or spastic bladder reaction [15,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation